Synovial tuberculosis masquerading as monoarticular inflammatory arthritis - Subramaniam, Krisnan Rao; Nor Hadi, Nor Hamizan; Zakaria@Mohamad, Zamzuri (Scientia Ricerca, 2019)
We report a case of a young girl presented with history of swelling over right knee for a period of 3 years which clinical, laboratory investigations and initial radiographic features were suggestive of auto-immune arthritis. Subsequently an open biopsy was done, although cultures were negative for MTB or NTM, histopathological examination (HPE) reported a chronic granulomatous inflammation which was highly suggestive of Tuberculosis (TB). She received anti-tuberculosis treatment for a total of one year and noted marked improvement which was evidently shown clinically and radiograhically. Musculoskeletal TB is known to be a great mimicker of other pathology. A high index of suspicion is needed especially in a TB-prone area.